A Retrospective Review of Temporal Bone Imaging With Respect to Bone-Anchored Hearing Aid Placement. Issue 1 (January 2017) - Baker, Aaron R.; Fanelli, David G.; Kanekar, Sangam; Isildak, Huseyin
Abstract : Objective: Current bone-anchored hearing aid (BAHA) guidelines recommend placement of the titanium implant 5 to 7 cm posterior to the ear canal. Previous studies show that bone conducted hearing is maximized the closer the transducer is to the cochlea. We aim to investigate the position of the sigmoid sinus with respect to BAHA implants to determine whether they may be safely placed closer to the ear canal in patients with chronic ear disease, enhancing the amplification available to the patient. Study Design: We performed a retrospective review of high-resolution temporal bone computed tomographies (CTs), comparing multiple measurements between ears with chronic ear disease and normal controls. Setting: Images were obtained at a single academic medical center. Patients: Eighty patients (160 ears) with temporal bone CTs performed between 2006 and 2009 were measured. Patients with chronic ear disease were identified by international statistical classification of diseases and related health problems, revision 9 code and confirmation by review of the imaging. Main Outcome Measures: Measurements were made on axial CT slices from a point 1 cm posterior to the sigmoid sinus to the posterior margin of the external canal. The squamous temporal bone thickness was also measured at this point. Results: Forty-seven patients (55 ears) had chronic ear disease. Distance from the posterior canal was significantly different between normal and diseased ears (36.3 mm versus 33.5 mm, p < 0.001). Squamous temporal bone thickness varied widely, and was similar between groups (6.9 mm versus 6.8 mm, p = 0.76). Conclusions: According to our data, titanium implants for bone-anchored hearing aids may be safely placed closer to the external canal than the current recommendations. This could allow for better transduction as well as sound localization in BAHA patients.